(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The different constituents of tobacco smoke have been linked to different diseased conditions. In this work, the histological effects of cigarette smoke on the cerebellum of adult male Wistar rats were studied. Sixteen Wistar rats with mean weight of 153.24 ± 4.12 g were grouped equally into four. The Control Group A was exposed to fresh air, while Groups B, C and D animals were each exposed to smoke from one, two and three sticks of cigarette respectively. Each stick of cigarette was completely consumed within an average duration of 11 minutes. Improvised smoking chambers were constructed and used for the exposure daily, while treatment lasted for 28 days. The animals were thereafter sacrificed by cervical dislocation, the cranium was exposed and the brain gently removed and weighed; the cerebellum was excised, weighed, and fixed in formol calcium, and subsequently processed for histological observation using the Haematoxylin and Eosin staining principle. Loss of weight and reduction in weight gain were noticed in the treatment groups, with corresponding reduction in cerebellar weights, in a dose-dependent pattern. Histology also revealed loss of white matter, reduction in thickness of cell layers and their cellular components. Increasing dosage of cigarette smoke could predispose to progressive compromise in the structural integrity and composition of the cerebellum, and this might result in cerebellar dysfunction.